The Influence Of Leadership And Motivation On Work Engagement With Competence As Variable Intervening (Case Study Of Gurusma N 2 Lahat) - M. Satria; Hardiyansyah Hardiyansyah; Nisma Aprini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to reveal the effect of leadership and motivation on work engagement with competence as an intervention variable (a case study of a teacher at SMA Negeri 2 Lahat). This research method uses a quantitative approach. The research respondents were honorary teachers at SMA Negeri 2 Lahat as many as 39 people. Collecting data using a questionnaire on honorary teachers at SMA Negeri 2 Lahat. The results of the study showed that leadership has a significant effect on honorary teachers' work engagement at SMA Negeri 2 Lahat. Motivation has a significant influence on the work engagement of honorary teachers at SMA Negeri 2 Lahat. Competence has a significant influence on honorary teachers' work engagement at SMA Negeri 2 Lahat. Leadership, Motivation, and Competence have a significant influence jointly on honorary teachers' Work Engagement at SMA Negeri 2 Lahat.